Peculiar pathological, radiological and clinical features of skull‐base de‐differentiated chordomas. Results from a referral centre case–series and literature review. Issue 5 (10th March 2020) - Asioli, Sofia; Zoli, Matteo; Guaraldi, Federica; Sollini, Giacomo; Bacci, Antonella; Gibertoni, Dino; Ricci, Costantino; Morandi, Luca; Pasquini, Ernesto; Righi, Alberto; Mazzatenta, Diego
Abstract : Aims: De‐differentiated chordoma is an uncommon and incompletely characterised aggressive neoplasm. Only a few cases originating from the skull base have been reported. Methods and results: All consecutive cases of skull‐base de‐differentiated chordomas treated surgically in a referral centre from January 1990 to June 2019 were retrospectively evaluated to assess peculiar pathological, radiological and clinical features. Patient data were retrieved from paper and electronic records. Six cases (two male, four female; mean age at surgery = 46 years, range = 35–64), treated surgically at our institution were identified. Transformation to de‐differentiated chordomas occurred after radiation therapy in three cases (mean = 13.6 years after treatment, range = 5–25), two during tumour progression, while one was de‐novo . Magnetic resonance imaging and surgical examination revealed the presence of two different tumour components, corresponding to the conventional and de‐differentiated portion on histological examination. The de‐novo case presented a PIK3CA mutation. DNA methylation analysis revealed consistent epigenetic changes in TERT, MAGEA11 and UXT . Prognosis was poor, as five of six patients died after surgery and radiation therapy, with a mean overall survival of 29 months (range = 11–52). Conclusions: Skull‐base de‐differentiated chordomas are extremely rare and aggressive neoplasms with characteristic magnetic resonance imaging, surgical and histological features. Therefore, an early and accurate histological diagnosis is of paramount relevance. Molecular analysis appears promising to define mechanisms involved in tumour de‐differentiation.